2014
DOI: 10.3167/trans.2014.040203
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Electric Cars as Socio-technical Mobility Experiments

Abstract: This article considers electric cars as socio-technical experiments in meeting mobility requirements. There have been numerous trials and government incentives to promote such vehicles, but with a notable lack of success. The article thus seeks to address an urgent need to understand such “transition failure,” which may ultimately impact upon how progress is measured in sociotechnical transitions. Presenting results from a recent research project, it is suggested that shared usage models hold greater potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…EVs are still often seen as primarily an urban solution; however, more recent research has shown that EVs can be equally useful in rural settings (Newman et al, 2014a, b, c). In much of rural Europe, the distance from a typical farm or village to the nearest market town and back is normally well within the range of an EV, and other types of alternative short range vehicle, such as the ‘voitures sans permis’ (as in France many can be driven without a driver’s licence) popular in rural parts of France – so-called L-Category microcars – are also primarily found in rural areas, despite their limited range.…”
Section: Transitioning To An Ev Regimementioning
confidence: 99%
“…EVs are still often seen as primarily an urban solution; however, more recent research has shown that EVs can be equally useful in rural settings (Newman et al, 2014a, b, c). In much of rural Europe, the distance from a typical farm or village to the nearest market town and back is normally well within the range of an EV, and other types of alternative short range vehicle, such as the ‘voitures sans permis’ (as in France many can be driven without a driver’s licence) popular in rural parts of France – so-called L-Category microcars – are also primarily found in rural areas, despite their limited range.…”
Section: Transitioning To An Ev Regimementioning
confidence: 99%
“…These activities have included industry conference events and corporate training workshops (e.g. Wells, , ).…”
Section: Deep Structural Sustainability: a Business Model Perspectivementioning
confidence: 99%